Pantropical spotted dolphin (Stenella attenuata attenuata) abundance estimates in Maui Nui, Hawaiʻi reveal small population in need of monitoring - Barber-Meyer, Shannon M.; Olson, Grace L.; Currie, Jens J. (Frontiers in Mammal Science, 2024)
Introduction: Recent minimum population estimates are critical for effective marine mammal conservation, yet such estimates are often lacking at the stock or management level. Throughout the Main Hawaiian Islands, pantropical spotted dolphins (PSD; Stenella attenuata attenuata) are comprised of a pelagic and three island-associated stocks (O‘ahu, 4-Islands, and Hawai‘i Island). The insular stocks, in particular, face multiple anthropogenic and natural threats such as vessel impacts, fisheries interactions, marine debris, climate change, and disease. Prior to this study, no abundance estimates of the 4-Islands (i.e., the Maui Nui region) PSD stock existed that were suitable for management use and inclusion in stock assessment report calculations. Methods: We generated annual mark-recapture abundance estimates of naturally marked adults in a POPAN-framework using photo-identification data collected from small-boat surveys during 2014–2022 in the Maui Nui region. We extrapolated these estimates to the wider population using dorsal fin mark rates. Results and Discussion: We collected data on 62 groups of PSD, throughout all months of the year, and with an average group size of 55.70 (SD = 17.31). We analyzed encounter histories of 174 distinct individuals. Annual recapture rate averaged 1.84 (SD = 1.32) with a maximum of 7. Individuals detected per year averaged 35.67 (SD = 21.16) with a maximum of 77 in 2017. Overall mark rate was 0.495 (SE = 0.010), resulting in total annual abundance estimates that averaged 154.87 (SE = 14.25) and ranged from 105 (SE = 13) in 2014 to 232 (SE = 31) in 2017. Although abundance estimates fluctuated, generally 250 animals or less used the study area each year and we found no overall evidence of a trend. Our benchmark results revealed a small population in need of monitoring given the numerous threats facing this stock, the uncertainty of their impacts, and the decreased resiliency and recovery potential of small populations to negative demographic and environmental stochastic events. Our findings, including documenting long-term site fidelity and year-round presence of PSD in Maui Nui, further signify this area as one of future research and conservation importance.